Discovery of a Potent Picolinamide Antibacterial Active against Clostridioides difficile - Speri, Enrico (ACS Infect Dis, 2020)
A major challenge for chemotherapy of bacterial infections is perturbation of the intestinal microbiota. Clostridioides difficile is a Gram-positive bacterium of the gut that can thrive under this circumstance. Its production of dormant and antibiotic-impervious spores results in chronic disruption of normal gut flora and debilitating diarrhea and intestinal infection. C. difficile is responsible for 12,800 deaths per year in the United States. Here, we report the discovery of 2-(4-(3-(trifluoromethoxy)phenoxy)-picolinamido)benzo[d]oxazole-5-carboxylate as an antibacterial with potent and selective activity against C. difficile. Its MIC(50) and MIC(90) (the concentration required to inhibit the growth of 50% and 90% of all the tested strains, respectively) values, documented across 101 strains of C. difficile, are 0.12 and 0.25 μg/mL, respectively. The compound targets cell wall biosynthesis, as assessed by macromolecular biosynthesis assays and by scanning electron microscopy. Animals infected with a lethal dose of C. difficile and treated with compound 1 had a similar survival compared to treatment with vancomycin, which is the frontline antibiotic used for C. difficile infection.